Penggunaan Cabri 3D terhadap Peningkatan Kemampuan Representasi Matematis Siswa - Rezkiyana Hikmah; Sri Rezeki; Bayu Jaya Tama (SAP (Susunan Artikel Pendidikan), 2019)
This reserch was condected to examine the mathematical representation ability of students who study with 3D cabry media and students who study with ordinary learning (not using 3D cabry media). This research is a quasi-experimental research. The sample of this research is grade VIII students of SMPN 1 in Cibinong. The research instruments used were pretest and posttest. Pretest and posttest are the same problem and are used as many times as at the beginning of the meeting and at the end of the meeting. The research data were analyzed using the mann whitney test and t test. The results of this study indicate that an increase in the mathematical representation ability of students who study with 3D cabry software is better than students who study with ordinary learning.